Acinetobacter spp. in neonatal sepsis: an urgent global threat - Pillay, Kamla; Ray-Chaudhuri, Anirban; O’Brien, Seamus; Heath, Paul; Sharland, Mike (Frontiers in Antibiotics, 2024)
Neonatal sepsis causes substantial morbidity and mortality, the burden of which is carried by lowincome countries (LICs). The emergence of multidrug-resistant pathogens in vulnerable neonatal populations poses an urgent threat to infant survival. Acinetobacter spp. are increasingly responsible for severe disease in neonates globally. The cause of this escalation remains unclear, but host, pathogen and environmental factors are all likely to contribute. Acinetobacter spp. strains are frequently resistant to the first line empirical treatment for neonatal sepsis as recommended by the World Health Organization (WHO), ampicillin and gentamicin, rendering these antibiotics ineffectual in many critically ill neonates. The resultant escalation to broader spectrum antibiotic regimens in neonatal intensive care units (NICUs) worldwide has led to the emergence of more resistant strains, including carbapenem-resistant Acinetobacter baumanii (CRAB), resulting in infections that are ever more difficult to treat. While some existing antimicrobial agents are under consideration for treatment of Acinetobacter spp. infections, the majority remain a long way from clinical use in neonates. Further research into the clinical phenotype of these infections, transmission dynamics and preventative measures are urgently needed to reduce neonatal deaths. This review aims to summarise the role of Acinetobacter spp. in neonatal sepsis, including host, pathogen and environmental factors, the global epidemiology and clinical features of the disease, the treatment options, and future research priorities.